Reproductive Health Education Based on Positive Youth Development through Youth Posyandu - Nisa, Alfiana Ainun; Sabrina, Alya Khairinnisa Nur; Rahmatammina, Risyda Nadila; Firahmadhani, Arifa; Katantri, Zavina; Lusiyanti, Verdiana; Alwana, Jamila Ghani; Rifli, Najwa Fauziyyah Nur; Nugroho, Efa (Universitas Airlangga, 2025)
Background: Adolescence is a critical transitional period marked by physical, emotional, and social changes, including sexual development, which may lead to risky dating behaviours. The Indonesian Demographic and Health Survey (SDKI) in 2017 reported that the majority of adolescents aged 15–17 have engaged in romantic relationships involving physical intimacy, ranging from holding hands to genital touching. Limited knowledge and a lack of positive attitudes toward reproductive health increase adolescents’ vulnerability to premarital sexual behaviour and its consequences, such as unwanted pregnancy, early marriage, sexually transmitted infections, and HIV/AIDS. Objective: This research aims to test the effectiveness of the “Ruang Kespro” educational program, which is based on the Positive Youth Development (PYD) framework, implemented through youth health posts in improving adolescents' knowledge and attitudes towards reproductive health. Methods: A descriptive quantitative research design with an educational intervention approach was used, involving 30 members of the Youth Red Cross (PMR) at SMA N 3 Semarang, selected purposively. The intervention was conducted in three sessions during October and November 2024. Data were collected through observation, documentation, pre-test, and post-test, and analyzed descriptively using SPSS. Result: The intervention led to a significant increase in knowledge scores from 87.00 to 98.33 (p = 0.001) and attitude scores from 86.17 to 99.67 (p = 0.001). These findings indicate that the PYD-based educational intervention through youth posyandu was effective in enhancing adolescents' knowledge and attitudes regarding reproductive health. Conclusion: The “Ruang Kespro” program successfully strengthened adolescents' understanding and positive attitudes toward reproductive health. It is recommended that schools and extracurricular organizations, such as PMR, continue and expand similar educational programs and youth health services. Future research should involve larger sample sizes to enhance population representation and statistical power for greater generalizability.